Exploring Grammar Learning Needs and Challenges: Insights from an Online Discussion Forum (Jurnal Sustainable, 2023)
This research article explores the grammar learning needs and challenges faced by English language learners through an analysis of questions collected from the online discussion forum. The forum, created by a group of researchers at Universitas Negeri Medan, serves as a platform for learners to seek guidance and support in their grammar learning journey. By conducting qualitative content analysis on 19 questions specifically related to grammar, common themes and patterns regarding grammar challenges were identified. The findings highlight areas of difficulty such as Subject-Verb Agreement, Direct and Indirect Speech, Punctuation (Hyphen usage), Relative Clauses, Understanding "Neither" and "Either", Verb Tenses,  Passive Voice, Direct Quotations vs. Paraphrasing in Academic Writing. Addressing these challenges through targeted explanations, examples, and recommendations can assist educators and language instructors in supporting learners in overcoming grammar difficulties and improving overall language proficiency. The insights derived from this study contribute to the development of effective instructional strategies tailored to learners' specific needs.